Monitoring of the Process of Changes of the Surface of Underground Waters and Level of Salinity in Farms of Syrdarya Region - Tashbekov U.T; Atabekov A.Sh (Zien Journals, 2023)
This article is devoted to the theoretical and practical aspects of monitoring on the basis of data obtained as a result of the analysis of the Syrdarya Regional Melioration Service in the reclamation state of irrigated soils, the collection of data collected on the groundwater level and salinity in recent years (2018-2019), a detailed study of the reclamation state of the soils of the territory. The authors emphasize the need to establish information support in the formation of a monitoring system for irrigated lands, the need to develop a local monitoring structure using observational data from the Syrdarya Regional Land Reclamation Service to achieve this goal. In order to use irrigation water economically in conditions of water scarcity, it was mentioned that the critical (acceptable) depth of groundwater should be determined based on the mineralization of groundwater (salinity level).
Keywords: Land and water resources; reclamation measures; collector; drainage